CHOOSING THE METHOD OF DEPOSITING THE BRASS LAYER ON THE STEEL SURFACE BEFORE RUBBERING THE CHEMICAL EQUIPMENT - Банник, Віктор; Зибайло, Сергій (SWorldJournal, 2025)
Rubber coatings are used mainly to protect the surface of chemical equipment and structures from the effects of medium aggressive environments. These coatings are also used as an elastic and impermeable underlayer for lining with artificial materials for